Punching Up in Stand-Up Comedy Speaking Truth to Power (Taylor & Francis, 2023)
phaticity, relatability, affect, awkwardness, cybernetics
English
Keywords: Humour; Media studies; Society and culture: general; phaticity, relatability, affect, awkwardness, cybernetics; thema EDItEUR::J Society and Social Sciences::JB Society and culture: general; thema EDItEUR::J Society and Social Sciences::JB Society and culture: general::JBC Cultural and media studies::JBCT Media studies; thema EDItEUR::W Lifestyle, Hobbies and Leisure::WH Humour